Vital Arctic Graphics: People and global heritage on our last wild shores - United Nations Environment Programme (United Nations Environment Programme, 2016)
The purpose of this report is to compile a number of “vital” Arctic graphics that describe the Arctic, the livelihoods of Arctic indigenous peoples and the future well-being of this region. It summarizes some key threats that endanger the future sustainability of the Arctic. The coastal regions are particularly important to the ecology and to the peoples of the Arctic and their current protection status is therefore given particular focus.